ISLAMIC BOARDING SCHOOL BUSINESS UNIT BUSINESS MANAGEMENT INNOVATION THROUGH DIGITIZING BUSINESS AND FINANCE - Ahmad Faisal, Yudi; Arum Kanti, Runita; Alamanda, Amelia Rizky (LPPM Univ. Ibn Khaldun Bogor, 2022)
This service activity aims to help pesantren to be better in their education prepare financial reports so that accountability and responsibility of the reports finances can be better accounted for to the public pesantren to preparation of financial statements based on Islamic boarding school accounting standards. Other purposes of This activity is to provide direction to pesantren administrators so that they can be more efficiently manage pesantren finances. Partner locations are in West Java and webinars carried out online. The results of the service show that 100% of the participants have never attend similar training.